History of wheat cultivars released by Embrapa in forty years of research - Caierão,Eduardo (2014)
In forty years of genetic breeding of wheat, Embrapa (Brazilian Agricultural Research Corporation) has developed over a hundred new cultivars for different regions of Brazil. Information regarding identification of these cultivars is often requested from Embrapa breeders. Data on year of release, name of pre-commercial line, the cross made, and the company unit responsible for indication of the cultivar are not always easily accessible and are often scattered throughout different documents. The aim of this study was to conduct a historical survey of all the wheat cultivars released by Embrapa, aggregating the information in a single document. Since 1974, Embrapa has released 112 wheat cultivars, including 12 by Embrapa Soybean - CNPSo (Londrina, PR), 14 by Embrapa Cerrado - CPAC (Brasília, DF), 9 by Embrapa Agropecuária Oeste - CPAO (Dourados, MS), and 77 by Embrapa Wheat - CNPT (Passo Fundo, RS).